2007
DOI: 10.1590/s1806-37132007000300015
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico imunológico da tuberculose: problemas e estratégias para o sucesso

Abstract: Tuberculosis remains a serious social and public health problem, affecting millions of people annually. The bacille Calmette-Guerin (BCG) vaccine, used prophylactically, does not impede the progression of the disease, which usually manifests as decreased cellular immunity. Early diagnosis, together with polychemotherapy, can control the dissemination of the tuberculosis infection. The current diagnostic methods present certain problems. Such problems include the low sensitivity of sputum smear microscopy, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 50 publications
(61 reference statements)
2
15
0
6
Order By: Relevance
“…[43]. No statistical difference, however, was found between this result and TST sensitivity (70–75%) in adults living in endemic countries such as Brazil [18]. However, the specificity of this test was quite high, around 90%, thereby corroborating the results obtained by a number of authors [15, 26, 39, 40, 43, 44] and suggesting that this method may be useful for the diagnosis of TB disease in children.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…[43]. No statistical difference, however, was found between this result and TST sensitivity (70–75%) in adults living in endemic countries such as Brazil [18]. However, the specificity of this test was quite high, around 90%, thereby corroborating the results obtained by a number of authors [15, 26, 39, 40, 43, 44] and suggesting that this method may be useful for the diagnosis of TB disease in children.…”
Section: Discussionsupporting
confidence: 77%
“…New strategies for the specific diagnosis of LTBI and TB disease in children are thus urgently needed to overcome the limitations of PPD [15,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Around 30-50% of TB patients are negative in the microscopy examination, and culture requires a long time for the growth of M. tuberculosis , which maybe lead to delay diagnosis [4,5]. The tuberculin skin test has long been used for the diagnosis of TB.…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts to develop an improved serological assay for TB have used this antigen [30, 76]. Early studies reported 89% sensitivity and 100% specificity in TBA patients [31].…”
Section: Human Tuberculosismentioning
confidence: 99%